Traffick - Hopkins, Ellen (Margaret K. McElderry Books, 2015)
Five teens victimized by sex trafficking try to find their way to a new life. There's Eden, the preacher's daughter who turns tricks in Vegas and is helped into a child prostitution rescue. Seth, the gay farm boy disowned by his father who finds himself without money or resources other than his own body. Whitney, the privileged kid coaxed into the life by a pimp and whose dreams are ruined in a heroin haze. Ginger, who runs away from home with her girlfriend and is arrested for soliciting an undercover cop. And Cody, whose gambling habit forces him into the life, but who is shot and left for dead. Now they are looking for a way out from the dark underbelly of the child trafficking trade.